Novel Regulators of Low-Density Lipoprotein Receptor and Circulating LDL-C for the Prevention and Treatment of Coronary Artery Disease - Cao, Guoqing; Konrad, Robert J.; Kowala, Mark C.; Wang, Jian (IntechOpen, 2012)
None